Peran Media Cetak Pada Pilkada Gubernur dan Wakil Gubernur NTB Tahun 2018 (Analisis Isi Berita Pilkada Gubernur dan Wakil Gubenur NTB Edisi 1-31 Maret 2018 Pada Harian Suara NTB) - Subhannur Subhannur; Yulanda Trisula Sidharta Yohanes; I Made Putra Suryantara (JCommsci - Journal Of Media and Communication Science, 2018)
The objectives of this study are: 1). to find out the neutrality of the local print media in the Suara Barat NTB in covering news regarding NTB governor—deputy governor election edition March 1-31 2018, 2). to find out how far the application of the Indonesian Journalists Journalist Code of Ethics by the Media Print of the Daily Voice of NTB on the election of the governor and deputy governor of NTB edition March 1-31 in 2018.The results shows that the frequency of the candidates reported was 51.9% of the Ali-Sakti pair, 24.03% of the pair of Akhyar-Mori, 13.4% of Zul-Rohmi pair and lastly the remaining 10.57% of the Suhaili-Amin pair.This calculation shows that the news of the NTB governor and deputy governor candidate pair in 2018 regional election leaned more towards the Ali-Sakti pair. Thus, the neutrality of the NTB voting media towards the pair of candidates and the application of the Indonesian Journalists Journalist Code of Ethics, especially in terms of presenting news in a balanced manner, still need improvement.Keyword: The Role of Media Print on Governor Election